2006
DOI: 10.1080/13697130600641282
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, estrogen and cognitive decline

Abstract: There are data to suggest an underlying link between homocysteine levels and cognitive decline. There is also evidence for a link between both the menopause transition and use of exogenous estrogen therapy and homocysteine levels. Clinical data do not support a role for exogenous estrogen in the prevention of dementia in older women; however, the 'window of opportunity' theory suggests that there is a need for randomized controlled trials to evaluate the role of estrogen in the early postmenopausal years to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 78 publications
0
2
0
2
Order By: Relevance
“…Methionine is a sulfur-containing essential amino acid that converts to homocysteine after donating the methyl group in cellular methylations (48). In vitro assays suggested that estrogen may regulate homocysteine levels through conjugation processes (49,50). Although the systemic interactions between methionine/homocysteine and estrogen (its receptors) are complex and unclear (51), based on clinical investigations comparing pregnant, premenopausal and postmenopausal women with estrogen replacement therapy (ERT) with age-matched men and postmenopausal women without ERT, the 3 rd National Health and Nutrition Examination Survey has recognized the inverse relationship between serum estrogen and homocysteine (52).…”
Section: Discussionmentioning
confidence: 99%
“…Methionine is a sulfur-containing essential amino acid that converts to homocysteine after donating the methyl group in cellular methylations (48). In vitro assays suggested that estrogen may regulate homocysteine levels through conjugation processes (49,50). Although the systemic interactions between methionine/homocysteine and estrogen (its receptors) are complex and unclear (51), based on clinical investigations comparing pregnant, premenopausal and postmenopausal women with estrogen replacement therapy (ERT) with age-matched men and postmenopausal women without ERT, the 3 rd National Health and Nutrition Examination Survey has recognized the inverse relationship between serum estrogen and homocysteine (52).…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown a modest decrease in homocysteine levels with raloxifene therapy. 35 In this study, we chose to consider words A and words B results together. Words A are simple words and words B are abstract words.…”
Section: Discussionmentioning
confidence: 99%
“…113,114 También puede ser un evento clave en el riesgo de demencia en el climaterio y la menopausia. 115 Hiperhomocistinemia y tejidos conectivos: autoinmunidad y osteoporosis…”
Section: Hiperhomocistinemia Y Neurodesórdenesunclassified